Proposição de uma metodologia para compras sustentáveis no Instituto Federal de Sergipe - Campus Lagarto - Bezerra, Diná Faustino (2017)
The Brazilian public institutions have adopted sustainable policies with socio-educational measures, green biddings are examples of promotion to sustainable development, through the use of social, environmental and economic criteria in the acquisition of goods, contracting of services and execution of works. The Federal Institute of Sergipe (IFS) Campus Legato makes small sustainable purchases, such as recycled paper, but it does not have a practice of sustainable purchases, given the lack of a facilitating method for sustainable bidding. The small purchases are made by the Rectory of the IFS, by adhesion of the Act of licitation (ride). This study, therefore, proposes the creation of a methodology of sustainable purchases in this Federal autarchy. This qualitative-descriptive research uses a semi-structured questionnaire to capture information from IFS employees about the use of sustainable biddings within the Institute, environmental perception and the main obstacles to sustainable procurement. The results point to the need to propose a sustainable purchasing methodology to guide the acquisition of goods and services. The purpose of this proposal is to streamline the purchasing process in the IFS, streamlining procurement steps and procedures. Thus, in line with the Sustainable Procurement Laws, the IFS is expected to exercise its purchasing power, which will lead to a socioenvironmental gain, the promotion of sustainable development.